Measurement of b hadron lifetimes in exclusive decays containing a J/ψ in pp collisions at √s=1.96 TeV. - Aaltonen, T; Álvarez González, B; Amerio, S; Amidei, D; Anastassov, A; Annovi, A; Antos, J; Apollinari, G; Appel, J; Apresyan, A; Arisawa, T; Artikov, A; et al. (2011)
We report on a measurement of b-hadron lifetimes in the fully reconstructed decay modes B(+)→J/ψK(+), B⁰→J/ψK*(892)⁰, B⁰→J/ψK(s)⁰, and Λ(b)⁰→J/ψΛ⁰ using data corresponding to an integrated luminosity of 4.3 fb⁻¹, collected by the CDF II detector at the Fermilab Tevatron. The measured lifetimes are τ(B(+))=[1.639±0.009(stat)±0.009(syst)] ps, τ(B⁰)=[1.507±0.010(stat)±0.008(syst)] ps, and τ(Λ(b)⁰)=[1.537±0.045(stat)±0.014(syst)] ps. The lifetime ratios are τ(B(+))/τ(B⁰)=[1.088±0.009(stat)±0.004(syst)] and τ(Λ(b)⁰)/τ(B⁰)=[1.020±0.030(stat)±0.008(syst)]. These are the most precise determinations of these quantities from a single experiment.